The culture factor in the training of foreign language teachers - Lozada Trimbath, Minnie (2006)
Students preparing to teach English need to understand the relationship between language and culture in order to avoid the misinterpretations that can arise when one is only guided by knowledge of the linguistic code when using the language. One aspect to consider when preparing English language teachers is their perception of the messages in English language teaching texts. In this essay we review examples of the perceptions of undergraduate students of Education at the Universidad Nacional Mayor de San Marcos, in relation to aspects of the way of life in English-speaking countries.